Modificaciones epigenéticas en clonación porcina - Buemo, Carla Paola (2016)
The somatic cells nuclear transfer technique (SCNT) or animal cloning, involves transferring the nucleus of a somatic donor cell into the cytoplasm of an oocyte that has been previously removed its nucleus, in order to obtain the necessary machinery to generate an embryo. However, it is a highly inefficient method and requires technical improvements.\nCloning has various applications in animal production. However, is still not entirely clear the mechanisms of nuclear remodeling and reprogramming that must suffer to become an embryo. A variety of factors probably contribute to this inefficiency, from the quality of oocytes to the type of donor cell. The failure to adequately reprogram the transplanted nucleus could be due to a deficient imprinting in somatic nuclei reconstituted embryo. To resolve the reprogramming failures we utilized in embryos the embryo aggregation technique and applied drugs that modify the epigenetic.\nAt the beginning of this study, partenogenetics embryos were used with these drugs that induce changes in methylation and histone acetylation, obtaining a combination of drugs (1 uM 5 Azacitidine + 1 uM PD0325901) which showed a tendency to increase in vitro embryo development. Subsequently, we continued to perform embryo aggregation, generating two groups: (1x) control and (3x) aggregates. The aggregated embryos increased in vitro development rates not involving a greater use of oocytes, also increased size measured by embryonic diameter, however, no statistically differences were found in the number of cells, apoptosis cell or DNA fragmentation between both groups.\nWhen we worked in swine clones, embryo aggregation in the one cell stage showed that were not required additional oocytes to produce higher rates of blastocyst resulting in an increase in the diameter and number of embryonic cells, while the level apoptosis was statistically lower in 3x aggregates embryos . This could prove partial compensation possibly caused by the combination of three different epigenetically embryos that had higher pluripotency gene expression . Moreover, by improving in vitro development, number of cells, embryonic diameter and decrease levels of apoptosis was improving embryonic reprogramming, obtaining better quality embryos.\nIn the last chapter of this thesis, we combined the embryo aggregation method and the use of drugs that induce epigenetic modifications in the early embryo development. This was encompass several aspects involving nuclear reprogramming, gene expression, showing marks relative to histones and DNA methylation. As a result, the treated 3x group showed an increase in embryonic size without involving changes in cell number. Also it showed an increase in gene expression related to trophoblast, involved in embryonic placentation, as in antiapoptotic genes and in the MAPK pathway genes involved.\nAnother change was displayed in the redistribution of acetylated histone H3 lysine 27 (H3K27ac). This is preferably located in the nuclear perisferia. Histone H3 with a methyl group at lysine 4 (H3K4me1) did not modify their distribution within the core, showing a homogeneous distribution. Regarding DNA methylation, Oct4 and Dnmt1 presented a marked demethylation, showing that the drug 5 Azacitidine, acting on methylation, generated changes in the embryos.\nIn conclusion, this work generated a contribution to the study of embryonic reprogramming that must suffer embryos during cloning, covering different variables that affect the reprogramming process.